Livelihood Transformation and Adaptation among Tharu Communities in Sahuraha, Chitwan, Nepal (Pragnya Sarathi, 2026)
This study examines the livelihood transformation and adaptation among the Tharu living in the surrounding area of Chitwan National Park. The objective of this study is to analyze the perception of the Tharu people living in Sahuraha related to the transformation and adoption of their livelihood due to the tourism business. The primary focus of this study is to highlight the impact of Chitwan National Park and the tourism business of Sahuraha on economic, socio-cultural and environmental aspects, as well as the livelihoods of the people. Face-to-face interviews, key informant interviews, and focus group discussions were used to gather data. The data were collected from the two traditional Tharu villages, Sahuraha and Malpur of Ratnanagar Municipality. A qualitative research design was used to analyze the data collected from the field. In total, 20 individuals participated in this study, including 10 who participated in face-to-face interviews, 3 key informant interviews, and 7 individuals in focus group discussions. From the analysis of the data, it is found that Chitwan National Park and the conservation policy led to a change in the traditional livelihood patterns of the Tharu people living in the study area. There found a transformation in socioeconomic and cultural situations as well as livelihood pattern. Environmental factors and social factors are directly affected in the sustainable livelihood of the people because in the current situation, they cannot continue the traditional agriculture-based livelihood. Benefit sharing is the main problem in bringing positive changes to the livelihood pattern. A benefit-sharing policy is necessary to preserve the traditional identities of the Tharu people, which are in the process of shifting due to the pressure of Chitwan National Park and the tourism business of Sahuraha.